SECONDARY PREVENTION OF STROKE IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION: THE CLINICIANS’ VIEWPOINT - E. A. Drozdova (Рациональная фармакотерапия в кардиологии)
Atrial fibrillation is one of the main risk factor of ischemic stroke. Current problems of the management of patients with stroke due to non-valvular atrial fibrillation and secondary stroke prevention in these patients are considered. Data of own author’s observation for patients of this type during 6 months after discharge from the hospital are presented. The problems which patients faced with are analyzed. Comparative assessment of warfarin and dabigatran therapies is given.